Rwanda : Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Requests for Waivers of Nonobservance of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2005)
This paper focuses on Rwanda's Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF) and Request for Waiver of Nonobservance of Performance Criteria. Macroeconomic performance of Rwanda remains broadly on track. Real growth in 2004 is estimated at 4 percent, mainly driven by strong activity in construction, transport, and communication. Policy implementation remained satisfactory. All but two performance criteria for the fifth review were met. Both deviations were temporary, and IMF staff recommends waivers.